2015
DOI: 10.1002/pmic.201400602
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analyses of two reovirus T3D subtypes and comparison to T1L identifies multiple novel proteins in key cellular pathogenic pathways

Abstract: Viruses induce changes in the host to facilitate replication and evade the immune response. These changes are reflected by the host's proteome, including differences in protein abundance. Focusing on up and down regulated proteins after a virus infects the cell will lead to a characterization of the host response to infection, and may give insight into how viruses modulate proteins to evade host defense responses. We previously used SILAC to examine host proteomic changes in protein abundance in HEK293 cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…These were some of the earliest reported differences between laboratory reovirus strains. More recently, comparisons between T3D laboratory strains found that T3D C (from the Cashdollar laboratory) and T3D F/N (from the Nibert laboratory) exhibit different respiratory pathogeneses in vivo and in cell signaling in vitro (23,41). Surprisingly, however, similar in vitro replication kinetics were observed between T3D laboratory strains compared to date.…”
Section: Discussionmentioning
confidence: 93%
“…These were some of the earliest reported differences between laboratory reovirus strains. More recently, comparisons between T3D laboratory strains found that T3D C (from the Cashdollar laboratory) and T3D F/N (from the Nibert laboratory) exhibit different respiratory pathogeneses in vivo and in cell signaling in vitro (23,41). Surprisingly, however, similar in vitro replication kinetics were observed between T3D laboratory strains compared to date.…”
Section: Discussionmentioning
confidence: 93%
“…TNFRSF10C, which is a known p53-regulated DNA damage-inducible gene, was upregulated with adenosine treatment (Sheikh et al, 1999). Interestingly, several genes involved with viral pathogenesis including PEG10, MX1, IFI44, and DDX60 were upregulated after treatment with adenosine (Berard et al, 2015, Kaczkowski et al, 2012. Finally, adenosine treatment induced the expression of several genes implicated in the interferon gene response (IRF9, MX1, IFIT1) (Gerner et al, 2019).…”
Section: Extracellular Adenosine Downregulates Expression Of Putative...mentioning
confidence: 99%
“…But it is only as recently as 2007, that a T7 plasmid-based reverse genetics technique finally allowed to alter with relative ease the genome of reovirus and thus study the effect of predetermined changes on the viral multiplication cycle [19,20,21]. More recently, high-throughput approaches have also been used to extensively look at the effect of reovirus infection on either the cellular proteome [22,23,24,25] or transcriptome using microarrays [26,27,28,29,30,31] or more extensive RNA-seq approaches [32,33]. Altogether, these approaches are likely to shed new light on the complex interactions between the host cell and the virus, as discussed below.…”
Section: Progress In Our Experimental Approachesmentioning
confidence: 99%